A Review Article on Rheumatoid Arthritis (RA) - Shaziya Tanzeem .T,; Shaguftha .T,; Farida Banu .S,; Karishma .S,; Hina Tousif .S,; Banny .S.V,; Sameera .P,; Meena .G, (Asian Journal of Pharmaceutical Research and Development, 2026)
Rheumatoid arthritis (RA) is a chronic systemic autoimmune inflammatory disorder primarily affecting synovial joints and leading to progressive joint destruction, disability, and reduced quality of life. In addition to joint involvement, RA is associated with multiple extra-articular manifestations involving the cardiovascular, pulmonary, ocular, and nervous systems. The etiology of RA is multifactorial, involving genetic predisposition, environmental factors such as smoking, and immune dysregulation. This review article provides a comprehensive overview of rheumatoid arthritis, including its historical background, etiology, pathophysiology, clinical manifestations, diagnostic criteria, and current therapeutic strategies. Special emphasis is given to the role of cytokines, immune cells, autoantibodies, and inflammatory mediators in disease progression. The review also discusses conventional and biological disease-modifying antirheumatic drugs (DMARDs), their mechanisms of action, and associated adverse effects. Understanding the complex pathogenesis and evolving treatment options of RA is essential for improving disease management, minimizing complications, and enhancing patient outcomes.